Conserved regulatory logic at accessible and inaccessible chromatin during the acute inflammatory response in mammals - Azad Alizada; Nadiya Khyzha; Liangxi Wang; Lina Antounians; Xiaoting Chen; Melvin Khor; Minggao Liang; Kumaragurubaran Rathnakumar; Matthew T. Weirauch; Alejandra Medina-Rivera; Jason E. Fish; Michael D. Wilson (Nature Communications, 2021)
Genetic elements that control inflammatory gene expression are not fully elucidated. Here the authors conduct a multi-species analysis of chromatin landscape and NF-κB binding in response to the proinflammatory cytokine TNFα, finding that conserved NF-κB bound regions are linked to enhancer activity and disease.